2007
DOI: 10.1002/cbdv.200790027
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory and Anti‐Tumor‐Promoting Effects of Triterpene Acids and Sterols from the Fungus Ganoderma lucidum

Abstract: A series of lanostane-type triterpene acids, including eleven lucidenic acids (3, 4, 9, 10, 13-19) and six ganoderic acids (20-22, 24, 26, 27), as well as six sterols (28-33), all isolated from the fruiting bodies of the fungus Ganoderma lucidum, were examined for their inhibitory effects on the induction of Epstein-Barr virus early antigen (EBV-EA) by 12-O-tetradecanoylphorbol-13-acetate (TPA) in Raji cells, a known primary screening test for anti-tumor promoters. All of the compounds tested, except for ganol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(82 citation statements)
references
References 16 publications
1
80
0
1
Order By: Relevance
“…Liu et al (31) also reported that ganoderic acid D, ganoderiol A, lucidumol B and ganodermadiol inhibited 5α-reductase activity of rat microsomes. Akihisa et al (30) also showed that ganoderic acid C1 and ganoderic acid C2 have inhibitory effects on the induction of Epstein-Barr Virus early antigen. Liu et al (33) recently showed that ganoderol B has the ability to bind to the androgen receptor, inhibit androgen-induced growth of prostate cancer cells and suppress re-growth of the ventral prostate induced by testosterone in rats.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Liu et al (31) also reported that ganoderic acid D, ganoderiol A, lucidumol B and ganodermadiol inhibited 5α-reductase activity of rat microsomes. Akihisa et al (30) also showed that ganoderic acid C1 and ganoderic acid C2 have inhibitory effects on the induction of Epstein-Barr Virus early antigen. Liu et al (33) recently showed that ganoderol B has the ability to bind to the androgen receptor, inhibit androgen-induced growth of prostate cancer cells and suppress re-growth of the ventral prostate induced by testosterone in rats.…”
Section: Discussionmentioning
confidence: 98%
“…The active GA-H is hydroxylated at position 3 and GA-A at position 7 and 15; whereas inactive GA-F is not hydroxylated. In addition, other triterpenes with hydroxyl or acetoxy groups at the positions 3, 7 and/or 15 such as ganoderic acid C1, ganoderic acid C2 (30), ganoderic acid D (31), ganoderic acid T (20), ganoderic acid X (19), ganoderic acid Y (32), ganoderiol A (31), ganoderol B (32,33), lucidumol B and ganodermadiol (30,31) were shown to have inhibitory biological activity. Shiao (34) demonstrated that several Ganoderma triterpenes with hydroxyl or acetoxy groups in these positions were cytotoxic to hepatoma cells and inhibited histamine release, cholesterol synthesis, and farnesylation of Ras protein.…”
Section: Discussionmentioning
confidence: 99%
“…A number of major components essential for our health have been identified in the noni plant: namely, scopoletin, octoanoic acid, potassium, vitamin C, terpenoids, alkaloids, anthraquinones, β-sitosterol, carotene, vitamin A, flavone glycosides, 18,19) . The noni plant was also reported to have a broad range of therapeutic effects, including antibacterial, antiviral, antifungal, antitumor, antihelmin, analgesic, hypotensive, anti-inflammatory, and immune enhancing effects 18,[20][21][22] . The primary indigenous use of the noni plant is to apply the leaves as a traditional topical treatment to promote wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…This prompted us to seek for new therapeutic options with better efficacy and less side effect for tumor treatment. Recently, medicinal fungi have attracted much attention and generated great interest for its potential applications in the cancer therapy field (3)(4)(5)(6). This kind of natural products are promising candidates which display little toxicity and low side effect, suggesting their certain advantage over the chemotherapeutic agents (7).…”
Section: Introductionmentioning
confidence: 99%